Influence of Fluid Effect on Virtual Simulation of Otolith Movement. Issue 1 (August 2021) - Kong, Lingyi; Wu, Jun; Feng, Mingjie; Liu, Zhaobang; Yang, Xiaoguo
Abstract: More and more physics engines are used to simulate the dynamics between two rigid bodies. However, it is still unknown whether physics engine is suitable for computing the physical information of objects with fluid effect, such as the trajectory and collision dynamics of otolith in semicircular canal in benign paroxysmal postural vertigo (BPPV). The purpose of this study is to determine whether the fluid effect in Bullet physics engine has an impact on the movement data of otoliths in semicircular canal. Based on the experimental data obtained previously, we discuss the position and trajectory of the otolith when it falls in the Dix-Hallpike test. Root Mean Square Error (RMSE) is used to evaluate the static position of otolith under two conditions, and the RMSE is 0.716. We found that the initial position of otolith is affected by fluid effects, but the final static position and trajectory of otolith is similar (x=-5.838±0.294, y=19.348±0.143, z=-9.540±0.635). The experimental results show that the fluid effect does not affect the experimental results of the Dix-Hallpike test, and it has sufficient applicability for the evaluation of BPPV diagnostic methods.